Malaysian disaster medicine research: a bibliographic study of publication trends - Adnan, Mohd Syafwan; Hart, Alexander; Hertelendy, Attila J.; Tin, Derrick; Abelanes, Sally-Mae; Issa, Fadi; Ciottone, Gregory R. (Cambridge University Press, 2022)
Introduction: Despite the increasing risks and complexity of disasters, education for Malaysian health care providers in this domain is limited. This study aims to assess scholarly publications by Malaysian scholars on Disaster Medicine (DM)-related topics. Methodology: An electronic search of five selected journals from 1991 through 2021 utilizing multiple keywords relevant to DM was conducted for review and analysis. Results: A total of 154 articles were included for analysis. The mean number of publications per year from 1991 through 2021 was 5.1 publications. Short reports were the most common research type (53.2%), followed by original research (32.4%) and case reports (12.3%). Mean citations among the included articles were 12.4 citations. Most author collaborations were within the same agency or institution, and there was no correlation between the type of collaboration and the number of citations (P = .942). While a few clusters of scholars could build a strong network across institutions, most research currently conducted in DM was within small, isolated clusters. Conclusion: Disaster Medicine in Malaysia is a growing medical subspecialty with a significant recent surge in research activity, likely due to the SARS-CoV-2/coronavirus disease 2019 (COVID-19) global pandemic. Since most publications in DM have been on infectious diseases, the need to expand DM-related research on other topics is essential